Analysis Of Student Perception Of Course Conversion At Origin University - Sanggam Pardede; Dearlina Sinaga; Nova Yunita Sari; Marihot Manullang; Grendy Mathew Valentino Purba (JURNAL PENDIDIKAN IPS, 2023)
This study aims to describe and explain the conversion of cross-major courses taken at the independent student exchange. This study used a qualitative method with 10 key informants, namely students participating in student exchanges at Atma Jaya Catholic University of Indonesia from the Teaching and Education Faculty and supporting informants, namely 4 lecturers from Atma Jaya Catholic University of Indonesia Jakarta. Primary data was taken using structured interviews. Techniques Data analysis in this study was carried out using the Miles model with data reduction, data presentation, drawing conclusions and triangulation. The results of the study prove that the courses that are converted are different from the courses taken at the receiving university from the courses at the original university. This research is still limited because it only examines independent student exchange students from the Teaching and Education Faculty, so recommendations for further research can hopefully examine all students at the receiving university.